FACTORS OF SUBJECTIVE WORK FATIGUE ON SERVICE WORKERS DOCKING PT PAL INDONESIA (PERSERO) - Yola Bella Arfani; Ratih Damayanti (Universitas Darussalam Gontor, 2019)
Fatigue was a feeling of tiredness and a decrease in alertness to workers caused by psychological and physical factors. Fatigue will reduce performance and increase the level of work errors. The purpose of this study was to analyze the internal factors and external factors of subjective work fatigue on service workers docking maintenance division in PT PAL Indonesia (Persero). This study was an observational study with cross sectional design. The subject in this study was the total population (18 workers). The independent variables in this study were internal factors (age, working period, and nutritional status) and workload. Dependent variables were subjective work fatigue that measured by the International Fatigue Research Committee (IFRC) 30-item questionnaire general fatigue symptoms. The results of this study showed that the most fatigue felt by workers was moderate fatigue (50%). Moderate fatigue were experienced by workers ranging in age from 25 to 32 years (57.1%) with a working period of 24-32 years (54.5%), excessive nutritional status (50%), and light workload (54.5%). The conclusion of this study were that the more age increases, the longer the working period, the more nutritional status increases the fatigue of work experienced. The lighter the workload, the more work fatigue increases, it is caused by factors outside of work. Keywords: Subjective Work Fatigue, Internal Factor, External Factor